Piomiosite tropical: apresentações atípicas - Gaiolla, Paula Schmidt Azevedo [UNESP]; Matsui, Mirna [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Paiva, Sérgio A.R. [UNESP]; Inoue, Roberto M.T. [UNESP]; Okoshi, Marina Politi [UNESP]; Morceli, Mauricio [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2004)
A piomiosite tropical é uma infecção primária dos músculos, que ocorre principalmente em países tropicais. Inicialmente, suas manifestações são leves e inespecíficas, o que dificulta o diagnóstico. A história natural dessa doença costuma ser benigna, com raras complicações. Essa apresentação descreve quatro casos de piomiosite, com manifestações e complicações peculiares.

Tropical pyomyositis is a primary infection of the skeletal muscles, that occurs mainly in tropical countries. At onset its manifestation is nonspecific, thereby hindering the diagnostic. The natural history of this disease is commonly benign, with rare complications. This presentation describes four cases of pyomyositis with peculiar manifestations and complications.
Tropical pyomyositis: atypical presentations
Keywords: Piomiosite tropical; Miosite; Staphylococus aureus; Abcesso muscular; Tropical pyomyositis; Myositis; Staphylococcus aureus; Muscle abscesses